2010
DOI: 10.1002/maco.201005678
|View full text |Cite
|
Sign up to set email alerts
|

The co‐operative effect of chloride ions and some natural extracts in retarding corrosion of steel in neutral media

Abstract: Effect of lupine and damsissa extracts on the corrosion of steel in 0.5 M Na2SO4 solution free from and containing 0.01 or 0.1 M NaCl were examined by potentiodynamic and electrochemical impedance spectroscopy techniques. Potentiodynamic polarization curves measurements indicated that damsissa and lupine extracts behave as anodic type inhibitors. Nyquist impedance plots showed type of distorted semicircle whose size increases with increasing concentrations of lupine or damsissa extract. Increasing chloride ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Effect of lupine on the corrosion of steel in 0.5 M Na 2 SO 4 solution free from and containing 0.01 or 0.1 M NaCl was examined by potentiodynamic and electrochemical impedance spectroscopy techniques. Potentiodynamic polarization curves measurements indicated that lupine extract behaves as an anodic type inhibitor [14]. Effect of lupine on the corrosion of zinc in neutral, alkaline and acidic media was examined by potentiodynamic and electrochemical impedance spectroscopy techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Effect of lupine on the corrosion of steel in 0.5 M Na 2 SO 4 solution free from and containing 0.01 or 0.1 M NaCl was examined by potentiodynamic and electrochemical impedance spectroscopy techniques. Potentiodynamic polarization curves measurements indicated that lupine extract behaves as an anodic type inhibitor [14]. Effect of lupine on the corrosion of zinc in neutral, alkaline and acidic media was examined by potentiodynamic and electrochemical impedance spectroscopy techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The studied plant materials include leaf extracts of Occimum viridis, Telferia occidentalis, Azadirachta indica and Hibiscus sabdariffa, as well as extracts from the seeds of Garcinia kola. The effect of lupine and damsissa extracts on the corrosion of steel in 0.5 M Na 2 SO 4 solution free from and containing 0.01 or 0.1 M NaCl were examined by potentiodynamic and electrochemical impedance spectroscopy techniques [10]. Also, olive leaves extract was studied as scale and corrosion inhibitor for steel surface in brine solution [11].…”
Section: Introductionmentioning
confidence: 99%
“…In the recent past, there has been a great improvement in the development of natural corrosion inhibitors . Plant extracts such as Croton cajucara , Bamboo , Artemisia pallens , Dendrocalamus brandisii , Salvia officinalis , lupine and damsissa extracts , etc., were reported as good corrosion inhibitors. In our laboratory itself we have reported that extracts of Solanum nigrum , Rauvolfia serpentina , Solanum tuberosum , Calotropis procera , Piper nigrum , Strychnos nux‐vomica , Datura stramonium , Datura metel , Ervatamia coronaria and extracts of marine algae viz., Caulerpa racemosa , Hydroclathrus clathratus , Spirulina platensis posses excellent corrosion inhibitive effects.…”
Section: Introductionmentioning
confidence: 99%